Exploring the antifungal properties of spent coffee extracts to produce Mold Resistant Gypsum Plaster Boards (MRGP) - Nursalik, Fahad A. (2020)
This study was conducted to explore the use of Spent Coffee Extracts (SCE) that are derived from the Spent Coffee Grounds (SCG) which are waste by products of Coffee Shops around Davao City. Although SCG can be a viable source of fertilizer, in its raw form, it can cause harm to plant life as it releases hydroxycinnamates, which were mainly different derivatives of chlorogenic acid (caffeoylquinic acids) and ferulic acid. The researcher extracted SCE from SCG and used it as an additive to a Lightweight Gypsum Board product. The efficacy of SCE as a mold retardant was tested using ASTM D3273 and ASTM D2020 test procedures. The following concentrations were used for the testing: 5%,25% 50%, and 100%. These replaced the water that was needed for the curing of the Lightweight Gypsum Plasterboard. An unexpected result of the SCE in the formulation of the Lightweight Gypsum Board is its properties as a retarder. The Plaster of Paris hardened at different rates depending on the concentration of the SCE, where the higher the formulation, the longer the curing time. The results of the ASTM D2020 and ASTM D3273 concluded that a 5% concentration showed 4.05% of mold growth on the surface while the control sample had 61.37%. The 15% and 25% concentrations showed growth of more than 19% and was deemed unfit for mold retardation. The author concludes that a 5% SCE concentration is a viable alternative to synthetic biocides with applications in the Drywall industry. Other uses for this compound could be seen in the wallpaper industry as well as other finishes that would require mold resistive properties like paint.